Regional impact of COVID-19 on the production and food security of common bean smallholder farmers in Sub-Saharan Africa: Implication for SDG's - Nchanji, Eileen Bogweh; Lutomia, Cosmas Kweyu (Elsevier, 2021)
Concerns about the implications of COVID-19 on agriculture and food security in Sub-Saharan Africa abound. Containment measures in response to the pandemic have markedly different outcomes depending on the degree of enforcement of the measures and the existing vulnerabilities pre-COVID. In this descriptive study, we document the possible impacts of the pandemic on bean production and food security using data collected from March to April 2020 in eleven countries in four sub-regions in Sub-Saharan Africa. The results reveal that COVID-19 created significant bean production challenges across the sub-regions, including low access to seed, farm inputs, hired labor, and agricultural finance. We also show that COVID-19 threatens to reverse gains made in the achievement of Sustainable Development Goals number 1 and 2. Countries in Southern and Eastern Africa are likely to suffer temporal food shortages than those in Western and Central Africa. Although governments have responded by offering economic stimulus packages, much needs to be done to enable the sub-sector to recover from ruins caused by the pandemic. We recommend building sustainable and resilient food systems through strengthening and enabling public-private partnerships. Governments should invest directly in input supply systems and short food supply chains through digital access and food delivery.